Lineage Relations in The Axiology of Islamic Law (Hubungan Nasab dalam Aksiologi Hukum Islam) - Rahmat Nugroho; Achmad Khudori Soleh; Luthfi, Muhammad Ilzam (STAI Ali bin Abi Thalib Surabaya, 2023)
In Islamic law, knowing one's lineage and preserving it plays a crucial role, as lineage occupies the fourth position among the five necessities (al-ḍaruriyyat al-khamsa). Without knowing the lineage relationship, it would be difficult for us to identify an individual and prevent someone from falsely claiming a lineage. This research aims to explore the virtuous values inherent in Islamic law concerning kinship relations. Furthermore, what is its relevance to axiology within the realm of philosophical inquiry? These questions are intriguing for investigation. To achieve this objective, the researcher adopts a qualitative descriptive methodology, where the data collection involves a literature review method focusing on relevant sources related to the problem being discussed. The findings of this study indicate that: (1) Lineage refers to kinship relationships, which come in various forms. (2) Axiology in philosophy studies value-related matters, encompassing ethics, aesthetics, and religion. (3) Similar to axiology, lineage holds both positive and negative values. Positive values of lineage include personal identity, honor, motivation, and exemplary behavior. On the other hand, negative values of lineage encompass sectarianism/ethnic fanaticism, arrogance, belittling other lineages, refusing to recognize other lineages, and lack of pride in one's lineage.